MADRASAH HEAD SUPERVISION IN IMPROVING TEACHER DISCIPLINE AT MIN 11, ACEH TENGAH DISTRICT - Riza Mahara Riza Mahara (Jurnal Ikhtibar Nusantara, 2024)
In improving teacher discipline, it is strongly influenced by the role of the madrasah principal as a supervisor through academic supervision. Principals are required to be able to utilise and overcome together all the problems that occur in schools, thus leadership can influence others to achieve the desired goals. The purpose of this study was to find out about: (1) academic supervision in preparing madrasah programme. (2) obstacles faced by principals in improving teacher discipline. This research uses descriptive method with qualitative approach. Data were collected through observation guidelines, interview guidelines, and documentation. The subjects in this study were the principal and teachers of MIN 11 Central Aceh Regency. Data analysis techniques in this study using data reduction, data display and drawing conclusions. The results of this study indicate that: (1) academic supervision in the preparation of the programme is carried out at the beginning of the school year, involving teachers. academic supervision programmes are prepared based on the problems and needs of teachers. (2) the principal of MIN 11 Central Aceh Regency has obstacles in improving teacher discipline at school. This can be seen from the work ethic of teachers who are still weak, teachers live far from school, different educational backgrounds, so they lack administrative skills, both teacher administration and classroom administration. It is expected that school principals can provide encouragement and direction in their performance regarding teacher discipline, teacher commitment, teacher ability and teacher responsibility effectively and efficiently to improve teacher discipline in schools.